Stand Strong : you can overcome bullying (and other stuff that keeps you down) - Vujicic, Nick (WaterBrook Press, 2014)
"Born without arms or legs, Nick Vujicic knows what it's like to be different. And he knows what it's like to be bullied and to rise above it. In Stand Strong, Nick gives you strategies for responding to the bullies in your life, empowering you to feel stronger than you ever have felt before."